Pengembangan Aplikasi M-Learning Berbasis Android Sebagai Sarana Penunjang Pembelajaran Dalam Kelas - Budi Santoso; Bambang Tri Wahyo Utomo; Sri Anggraini Kusuma Dewi (LPPM UBHINUS MALANG, 2020)
The use of learning management software is increasingly widespread in the era of industry 4.0, but most of the software was developed in the time when the use of smartphones has not been widespread, so that the interface is designed for use on desktop computers. Although e-learning allows users to access lecture material remotely through web applications, user mobility is still limited because it depends on the position of the desktop where he works. Accesing the application using a smartphone is also not enjoyable due to poor performance and the screen is too cluttered with the menu, which is don’t fit with the small screen of the smartphone. This lead to less optimal use of the e-learning facilities by students. To overcome the above obstacles, this research designed an e-learning application interface with native applications on mobile devices. This e-learning mobile application consists of a backend that runs on the server and a frontend application on a smartphone device. As a backend to servers, chamilo-based online learning management software is used. Chamilo is an opensource online learning management software developed with php programming language. The mobile software was developed natively for android devices using the react native framework, a programing framework based on javascript programming language. Access to the database using SOAP-based webservice and RESTFUL API. It is expected that with this software students can access the lecture material more frequently due the simple and more intuitive interface without being hindered by complex menus, so that the level of absorption of learning material is higher.